Workload and quality of nursing care: the mediating role of implicit rationing of nursing care, job satisfaction and emotional exhaustion by using structural equations modeling approach - Fatemeh Maghsoud; Mahboubeh Rezaei; Fatemeh Sadat Asgarian; Maryam Rassouli (BMC, 2022)
Abstract Background Nursing workload and its effects on the quality of nursing care is a major concern for nurse managers. Factors which mediate the relationship between workload and the quality of nursing care have not been extensively studied. This study aimed to investigate the mediating role of implicit rationing of nursing care, job satisfaction and emotional exhaustion in the relationship between workload and quality of nursing care. Methods In this cross-sectional study, 311 nurses from four different hospitals in center of Iran were selected by convenience sampling method. Six self-reported questionnaires were completed by the nurses. The data were analyzed by SPSS version 16. Structural equation modeling was used to determine the relationships between the components using Stata 14 software. Results Except direct and mutual relationship between workload and quality of nursing care (P ≥ 0.05), the relationship between other variables was statistically significant (P < 0.05). The hypothesized model fitted the empirical data and confirmed the mediating role of implicit rationing of nursing care, job satisfaction and emotional exhaustion in the relationship between workload and the quality of nursing care (TLI, CFI > 0.9 and RMSEA < 0.08 and χ2/df < 3). Conclusion Workload affects the quality of the provided nursing care by affecting implicit rationing of nursing care, job satisfaction and emotional exhaustion. Nurse managers need to acknowledge the importance of quality of nursing care and its related factors. Regular supervision of these factors and provision of best related strategies, will ultimately lead to improve the quality of nursing care.